2005
DOI: 10.1095/biolreprod.104.036715
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Uteroplacental Perfusion Alters Uterine Arcuate Artery Function in the Pregnant Sprague-Dawley Rat1

Abstract: Evidence continues to implicate reduced placental perfusion as the cause of preeclampsia, initiating a sequence of events leading to altered vascular function and hypertension. The present study was designed to determine the influence of reduced uteroplacental perfusion pressure (RUPP) on the responsiveness of uterine arcuate resistance arteries. A condition of RUPP was surgically induced in pregnant Sprague-Dawley rats on Gestational Day 14. On Gestational Day 20, uterine arcuate arteries were mounted on a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 29 publications
9
44
1
4
Order By: Relevance
“…This theory is supported by observations made in the reduced utero-placental perfusion model (RUPP) in which the uterine blood flow of pregnant rats is surgically reduced. RUPP increases sensitivity to vasoactive factors at both local and systemic levels, which results in hypertension (Anderson et al, 2005;Crews et al, 2000). These findings were further substantiated by a recent study of placental gene expression in the Norway Brown rat (Goyal et al, 2010), a strain that exhibits significantly decreased trophoblast vascular invasion.…”
Section: Notch2mentioning
confidence: 72%
“…This theory is supported by observations made in the reduced utero-placental perfusion model (RUPP) in which the uterine blood flow of pregnant rats is surgically reduced. RUPP increases sensitivity to vasoactive factors at both local and systemic levels, which results in hypertension (Anderson et al, 2005;Crews et al, 2000). These findings were further substantiated by a recent study of placental gene expression in the Norway Brown rat (Goyal et al, 2010), a strain that exhibits significantly decreased trophoblast vascular invasion.…”
Section: Notch2mentioning
confidence: 72%
“…Studies in these animal models have led to the concept that reduction in the uteroplacental perfusion pressure and the ensuing placental ischemia/ hypoxia during late pregnancy may represent the initiating events that eventually lead to increased systemic vascular resistance and HTN-Preg. In support of this concept, studies (5,6,14,26,63) have demonstrated that reduction of uterine perfusion pressure (RUPP) in late pregnant rats is associated with significant increases in renal vascular resistance and BP; however, the vascular and cellular mechanisms involved have not been clearly elucidated.Vascular smooth muscle (VSM) contraction is triggered by an increase in intracellular free Ca 2ϩ concentration ([Ca 2ϩ ] i ) due to initial Ca 2ϩ release from the intracellular stores and maintained Ca 2ϩ entry from the extracellular space (39 -41, 51). Ca 2ϩ binds calmodulin to form a complex that activates myosin light chain kinase, causes myosin light chain phosphorylation, initiates actin-myosin interaction, and produces VSM contraction (30,62).…”
mentioning
confidence: 99%
“…A massa funcional da placenta tem sido reduzida experimentalmente por uma variedade de técnicas, incluindo embolização, carunculectomia, gestações múltiplas, redução do fluxo sanguíneo e inseminação ou transferência de embriões entre raças de diferentes portes (WALTON;HAMMOND, 1938;JOHNSON, 1995;CLARKE et al, 1998, GIUSSANI et al, 2003ANDERSON et al, 2005 Em ovinos e ratos, a restrição alimentar materna prejudicou o crescimento fetal intrauterino, e quando adultos apresentaram hipertensão e intolerância a glicose (ROBINSON et al, 2000). Anderson et al (2005Anderson et al ( , 2006 Análise estereológica da placenta e subsequente correlação com a estrutura e função desse órgão tem sido importante para avaliar relações feto -maternas na espécie equina (ALLEN et al, 2002a;VERONESI et al, 2010), e em outros mamíferos (MAYHEW et al, 2003;COAN et al, 2006;MAYHEW, 2006 , 1938;TISCHNER, 1987;WILSON et al, 1998;ALLEN et al, 2002a).…”
Section: Revisão De Literaturaunclassified
“…Anderson et al (2005Anderson et al ( , 2006 Análise estereológica da placenta e subsequente correlação com a estrutura e função desse órgão tem sido importante para avaliar relações feto -maternas na espécie equina (ALLEN et al, 2002a;VERONESI et al, 2010), e em outros mamíferos (MAYHEW et al, 2003;COAN et al, 2006;MAYHEW, 2006 , 1938;TISCHNER, 1987;WILSON et al, 1998;ALLEN et al, 2002a).…”
Section: Revisão De Literaturaunclassified